Fabrication of Ba0.95M0.05Li2Ti6O14 (M = Ag, Pb, Al) as high performance anode candidates for lithium secondary batteries. (20th February 2017) - Yu, Haoxiang; Yan, Lei; Qian, Shangshu; Li, Peng; Lan, Hua; Zhu, Haojie; Long, Nengbing; Shui, Miao; Shu, Jie
Graphical abstract: Highlights: A substitution of Ba by Ag, Pb and Al is conducted on BaLi2 Ti6 O14 . Metal doping is demonstrated as an effective method for BaLi2 Ti6 O14 . Ba0.95 Ag0.05 Li2 Ti6 O14 displays superior lithium storage capability. Ba0.95 Ag0.05 Li2 Ti6 O14 show high structural reversibility as lithium host material. Abstract: Using Ag, Pb and Al as dopants, Ba0.95 M0.05 Li2 Ti6 O14 is fabricated as advanced anode candidate for repeated lithium storage. Owing to smaller ionic radius, Ag +, Pb 2+ and Al 3+ are successfully introduced into the lattice of BaLi2 Ti6 O14, which results in the formation of high purity Ba-site doped Ba0.95 M0.05 Li2 Ti6 O14 (M = Ag, Pb, Al). Compared with the pristine sample, M-doped BaLi2 Ti6 O14 exhibits higher reversible capacity, better rate capability and superior cyclability. Especially for Ba0.95 Ag0.05 Li2 Ti6 O14, it presents the best electrochemical property among all the as-prepared samples. It can deliver a high reversible charge capacity of 149.1 mAh g −1 after 100 cycles at the current density of 100 mA g −1 with capacity retention of 92.27%. In contrast, BaLi2 Ti6 O14 only provides a lithium storage capacity of 126.9 mAh g −1 with capacity retention of 80.83%. In addition, its high structural stability and electrochemical reversibility are also demonstrated by in-situ X-ray diffraction observation. All these evidences show that metal doping may be an effective method to enhance the lithium storage capability of BaLi2 Ti6 O14 . Especially for Ba0.95 Ag0.05 Li2 Ti6 O14, it can be used as possible anode candidate for rechargeable batteries.